A novel epigenetic marker, Ten-eleven translocation family member 2 (TET2), is identified in the intractable epileptic brain and regulates ATP binding cassette subfamily B member 1 (ABCB1) in the blood–brain barrier. Issue 3 (1st March 2022) - Kong, Fan-Cheng; Lang, Li-Qin; Hu, Jie; Zhang, Xia-Ling; Zhong, Ming-Kang; Ma, Chun-Lai
ABSTRACT: Drug-resistant epilepsy (DRE) is a chronic condition derived from spontaneous changes and regulatory effects in the epileptic brain. As demethylation factors, ten-eleven translocation (TET) family members have become a focus in recent studies of neurological disorders. Here, we quantified and localized TET1, TET2 and 5-hydroxymethylcytosine (5-hmC) in the temporal lobe cortex of DRE patients (n = 27) and traumatic brain hemorrhage controls (n = 10) by immunochemical staining. TET2 and ATP binding cassette subfamily B member 1 (ABCB1) expression patterns were determined in the isolated brain capillaries of DRE patients. TET2 expression was significantly increased in the temporal cortical tissue of DRE patients with or without hippocampal sclerosis (HS) compared to control patients, while TET1 and 5-hmC showed no differences in expression. We also found that a particularly strong expression of TET2 in the vascular tissue of DRE patients. ABCB1 and TET2 have evidently higher expression in the vascular endothelium from the neocortex of DRE patients. In blood–brain barrier (BBB) model, TET2 depletion can cause attenuated expression and function of ABCB1. Data from a cohort study and experiments in a BBB model suggest that TET2 has a specific regulatory effect on ABCB1, which may serve as a potential mechanism and target in DRE. Graphical Abstract: uf0001